2002
DOI: 10.3386/w8852
|View full text |Cite
|
Sign up to set email alerts
|

Property Rights and Finance

Abstract: Which is the tighter constraint on private sector investment: weak property rights or limited access to external finance? From a survey of new firms in post-communist countries, we find that weak property rights discourage firms from reinvesting their profits, even when bank loans are available. Where property rights are relatively strong, firms reinvest their profits; where they are relatively weak, entrepreneurs do not want to invest from retained earnings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
276
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(295 citation statements)
references
References 0 publications
16
276
1
2
Order By: Relevance
“…2 This has put institutions squarely on the policy agenda, remaining methodological challenges notwithstanding (Przeworski 2004, Bardhan 2005, Third, use of firm level data provides an option to overcome the econometric and substantive limitations inherent in cross-country regressions. For Eastern European countries, the fact that firms reinvest their retained earnings in situations where property rights are strong but do not do so in environments characterized by weak property rights is interpreted as providing support to the hypothesis that property rights are more important than financing constraints (Johnson et al 2002). This is in line with the much greater relevance of property rights as compared to contracting institutions on economic growth that emerged from cross-country regressions (Acemoglu and Johnson 2005).…”
Section: The Importance Of Secure Property Rights and The Challenge Osupporting
confidence: 69%
“…2 This has put institutions squarely on the policy agenda, remaining methodological challenges notwithstanding (Przeworski 2004, Bardhan 2005, Third, use of firm level data provides an option to overcome the econometric and substantive limitations inherent in cross-country regressions. For Eastern European countries, the fact that firms reinvest their retained earnings in situations where property rights are strong but do not do so in environments characterized by weak property rights is interpreted as providing support to the hypothesis that property rights are more important than financing constraints (Johnson et al 2002). This is in line with the much greater relevance of property rights as compared to contracting institutions on economic growth that emerged from cross-country regressions (Acemoglu and Johnson 2005).…”
Section: The Importance Of Secure Property Rights and The Challenge Osupporting
confidence: 69%
“…26 When the protection of property rights is eroded, a first effect is to reduce the profits pertaining to productive entrepreneurship. 27 For instance, business owners will retain a smaller share of profits in their firms (Johnson et al 2002). A further effect is that entrepreneurship takes new forms, since opportunities to earn profits from unproductive entrepreneurship arise.…”
Section: Institutions and High-growth Firmsmentioning
confidence: 99%
“…The breadth of the country of origin of the firm sample also merits highlighting as there is only limited comparable work which has drawn upon a range of countries focused upon small businesses in emerging economies (Chhakravarty & Xiang, 2011). Other empirical work in this area focused upon post-communist countries (Johnson, et al, 2002) and Chinese firms in 2002 (Cull & Xu, 2005).…”
Section: Contributionsmentioning
confidence: 99%
“…Institutional factors have been acknowledged as significant for reinvestment decisions (Cull & Xu, 2005;Johnson, McMillan, & Woodruff, 2002) as well as repatriation of earnings (Lundan, 2006). Although Cull & Xu (2005) found that contract enforcement did impact upon reinvestment, they did not explore this within additional dimensions of corruption.…”
Section: Reinvestment Choicesmentioning
confidence: 99%